Massimo Torricelli's Obsession in Blanka Lipinska's 365 Days - Ilmi, Avita; Wahyono, Danu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
The research study titled "Massimo Torricelli's Obsession in Blanka Lipinska's 365 Days" was conducted to analyze the cause and effect of the main character's obsession in the novel. The research was motivated by the psychological theory of love and obsession proposed by Robert Stenberg, which emphasizes the importance of maintaining a healthy balance in relationships. The research problem focused on understanding Massimo Torricelli's obsession with Laura Biel and its implications for their relationship. A qualitative research design was used, utilizing a psychological perspective to analyze the main character's obsession. Data was collected from the novel "365 Days" and analyzed using Stenberg's obsession theory. Findings revealed that Massimo's obsession stems from a desire to possess and control Laura, rooted in past trauma and leading to controlling and manipulative behavior. Despite his flaws, Massimo demonstrated emotional depth and a willingness to connect with Laura on a deeper level. This study highlights the toxic dynamics in their relationship, and underscores the potential for growth and change. The implications of this study offer insight into the portrayal of love and relationships in literature as well as the importance of prioritizing healthy and balanced relationships. Keywords : Control, Love, Manipulative Behavior, Relationships, Toxic Dynamics